β-1,3-glucan modifying enzymes in Aspergillus fumigatus - Mouyna, Isabelle; Hartl, Lukas; Latgé, Jean-Paul (Frontiers in Microbiology, 2013)
In Aspergillus fumigatus like in other filamentous ascomycetes, β-1,3-glucan constitutes a prominent cell wall component being responsible for rigidity of the cell wall structure. In filamentous fungi, softening of the cell wall is absolutely required during conidial germination and hyphal branching. Because of the central structure of β-1,3-glucans, it is expected that β-1,3-glucanases play a major role in cell wall softening. Based on in silico and experimental data, this review gives an overview of β-1,3-glucan modifying enzymes in A. fumigatus genome and their putative role during morphogenesis.